Hematological Toxicities of Concurrent Chemoradiotherapies in Head and Neck Cancers: Comparison Among Cisplatin, Nedaplatin, Lobaplatin, and Nimotuzumab - Wu, Qiuji; Zhu, Chunmei; Zhang, Shuyuan; Zhou, Yunfeng; Zhong, Yahua (Frontiers in Oncology, 2021)
Background: Cisplatin-based concurrent chemoradiotherapy is standard of care for locally advanced head and neck cancers (LAHNC). Nedaplatin, lobaplatin and nimotuzumab have shown anti-cancer effect with less gastrointestinal toxicity and nephrotoxicity. However, the profile of hematological toxicities of these agents in combination with radiotherapy has not been fully illustrated. Methods: We retrospectively collected the clinical data of consecutive LAHNC patients treated by cisplatin-, nedaplatin-, lobaplatin-, and nimotuzumab-based concurrent chemoradiotherapy. Routine blood cell counts were obtained every 4 to 7 days. Hematological toxicities were graded according to the Common Terminology Criteria for Adverse Events (CTCAE) Version 5.0. Results: A total of 181 eligible LAHNC patients were assigned to nimotuzumab group (n = 34), cisplatin group (n = 52), nedaplatin group (n = 62) or lobaplatin group (n = 33). Among the four groups, nimotuzumab group displayed lightest hematological toxicities, followed by cisplatin group, nedaplatin group, and lobaplatin group. Lobaplatin was more likely to produce grade 3/4 leukopenia compared with cisplatin (48.5% vs 25.0%). Compared with cisplatin, nedaplatin and lobaplatin were more likely to cause grade 3/4 thrombocytopenia (nedaplatin 19.4% vs cisplatin 3.8%; lobaplatin 30.3% vs cisplatin 3.8%). Similarly, nimotuzumab group showed highest nadir levels among the four groups, followed by cisplatin, nedaplatin, and lobaplatin group. Moreover, concurrent platinum treatment and induction chemotherapy were risk factors of developing grade 3/4 hematological toxicities. Conclusion: Nimotuzumab-based concurrent chemoradiotherapy in head and neck cancers produced the lightest hematological toxicities, followed by cisplatin, nedaplatin, and lobaplatin. Patients should be given specific attention during concurrent chemoradiotherapy, particularly in the presence of previous induction chemotherapy.